Community Theater for Health Promotion in Japan - Sandhu, Hikari; Hirose, Naoki; Yui, Kazuya; Jimba, Masamine (Arts and Health Promotion: Tools and Bridges for Practice, Research, and Social Transformation, 2021)
This chapter describes the history of theater-based health promotion in Japan. It focuses on the grassroots health promotion movement led by Dr. Wakatsuki and his colleagues at Saku Hospital in Nagano prefecture in 1945, when health literacy among the local community was especially low. It is a significant piece of history because these works of theater engaged both the general population in the local community and medical professionals, and not only increased the health status of those living in the area but also established the community itself as a hub of health care in Nagano prefecture. The movement shares common ground with Augusto Boal’s “Theatre of the Oppressed,” as both aim to change the mindset of people in a community to liberate them from their current conditions. This work is relevant today because Wakatsuki’s medical dramas successfully empowered people in the Saku community and changed a mindset of villagers toward their health. This chapter highlights the benefit of such approaches and encourages all medical and health practitioners to take note of the fundamental impact of arts-based interventions, as well as how works of theater can positively transform people’s mindsets.